MAKSUD-MAKSUD TUHAN DALAM MENETAPKAN SYARIAT DALAM PERSPEKTIF AL-SYATIBI - Wahyuddin Wahyuddin (Syariah: Jurnal Hukum dan Pemikiran, 2014)
Maqashid al-Sharia is sharia purposes or secrets which are established by Allah. Accordingto al-Syatib, there are four purposes of Allah to determine the shariah: (1). For the benefit of peoplein the world and the hereafter. (2). To be understood. (3). As a taklif law that must be implementedand to eliminate hardship. (4). To comply and freed from the influence of the passions mukallaf. Thefirst mentioned purpose is the main aim, while other purposes only explains and details the firstpurpose. For the realization of such benefit, there are six essential components